2007
DOI: 10.1007/s11096-006-9042-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic outcomes of pharmaceutical services related to antibiotic use: a literature review

Abstract: Over the years, the number of studies and quality of methodology has increased. The most frequently observed outcomes with a positive impact were appropriateness of prescribing and cost savings. The vast majority of studies used multiple interventions, in conjunction with pharmacists' recommendations to physicians. Coupled with the use of practice guidelines or educational strategies, these interventions demonstrated a positive impact on economic or clinical outcomes. However, the data are still sparse and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 55 publications
(60 reference statements)
2
35
0
2
Order By: Relevance
“…Compared to other systematic reviews [6,8] examining the impact of clinical pharmacists on different diseases and different patient populations, very few studies could be identified that addressed the impact of clinical pharmacy services on SOT patients. However, clinical pharmacy services do exist for this specialised patient population, predominantly in the field of kidney and liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other systematic reviews [6,8] examining the impact of clinical pharmacists on different diseases and different patient populations, very few studies could be identified that addressed the impact of clinical pharmacy services on SOT patients. However, clinical pharmacy services do exist for this specialised patient population, predominantly in the field of kidney and liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical pharmacists who specialise in SOTs are also members of these multidisciplinary teams, and they address drug-related therapeutic issues in this population. Clinical pharmacy services have proven to be beneficial in the management of many diseases and special patient populations and have contributed to patient safety, reductions in drug-associated mortality and hospitalisations, and they have had an overall positive impact on patient care [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Existe la posibilidad de actuar sobre las conductas de uso de antibióticos y mejorarlas, pero resulta indispensable considerar el contexto en forma global y de manera integrada, involucrando a médicos, farmacéuti-cos y pacientes, y manteniendo las intervenciones periódicamente 19 . Sólo con perseverancia es posible cambiar los hábitos inadecuados de prescripción, dispensación y consumo, de allí que un cronograma anual de intervenciones, realizado por profesionales o Comisiones con experiencia en el tema de antibióticos, ajustado a las peculiaridades de cada área de salud y ejecutado de forma constante a lo largo de los años, sea en nuestra experiencia un forma eficaz de realizar una correcta política de antibióticos.…”
Section: Discussionunclassified
“…In addition, the availability of TDM remains limited for the most widely prescribed antibiotics, the betalactams [16]. This may explain why TDM studies on relevant outcomes including mortality and cost effectiveness are scarce and have produced mixed results [17][18][19]. A further explanation for this mixed effect is the fact that pharmacokinetic targets for plasma and effect site remain the subject of debate (see also the boxed text).…”
Section: The Problem Of Therapeutic Drug Monitoringmentioning
confidence: 99%